Tanggung Jawab Hukum Pihak Penjual Atas Penjualan Properti Tanpa Persetujuan Pemilik Properti - Siallagan, Nissy Asandrum; Habeahan, Besty (Innovative: Journal Of Social Science Research, 2024)
A seller is not allowed to sell property without the owner's consent, as this constitutes a violation of both civil and criminal law. Under civil law, such a sale may be considered an unlawful act causing losses to the property owner. To annul the transaction and/or seek compensation from the seller, the property owner can file a legal lawsuit. From a criminal law perspective, if evidence indicates malicious intent in conducting the unauthorized sale, this act can be categorized as embezzlement under the Indonesian Penal Code (KUHP). If it is proven that the seller sold the property without the owner's consent, they may face criminal penalties, including imprisonment and/or fines. This article discusses the legal implications that may arise, as well as the legal actions property owners can take to protect their rights, including through civil litigation and criminal reporting processes.